Diversity at Landscape Level to Increase Resilience. A Review - Turyasingura, Benson; Mwanjalolo, Majaliwa; Ayiga, Natal (East African Journal of Environment and Natural Resources, 2022)
Tree species increases the number of ecological niches and associated species such as understory plants and animals hence, increased landscape ecosystem diversity. Rapid environmental and economic changes are posing serious dangers to ecosystems and economic systems around the world. This has resulted in the extinction of species, droughts, and price fluctuations in agricultural products. The aim of this review is to document landscape diversity and ecosystem resilience as a tool for natural resources management. The species from one ecosystem's functional group may temporarily support a functional group in another ecosystem, significant variety can help to maintain ecological stability. Hence, building on these insights, diversity at landscape level is paramount to promoting resilient livelihoods as a means of improving the health and functioning of socio-ecological systems, as well as a mechanism for achieving food security. The study concludes that there should be involving many actors in a landscape management aspect to stimulate knowledge exchange and training.
Keywords: Diversity; Resilience; Landscape; Biodiversity; Environment